T- and B-lymphocytes subpopulations in the early and advanced rheumatoid arthritis - A. V. Martynova; T. V. Popkova; A. P. Aleksankin; G. I. Gridneva; E. V. Gerasimova; Yu. N. Gorbunova; A. S. Semashko; A. M. Lila (Современная ревматология)
Objective: to evaluate changes in T- and B-lymphocyte subpopulations at different stages of rheumatoid arthritis (RA).Patients and methods. The study included 53 patients with a definite RA diagnosis according to the 2010 ACR/EULAR criteria (mean age 54.2 [47; 62] years). Group 1 included 27 patients (25 women and 2 men) without history of synthetic disease modifying anti-rheumatic drugs (sDMARDs) intake, group 2 included 26 patients (22 women and 4 men) receiving sDMARDs (methotrexate or leflunomide). The control group consisted of 29 healthy volunteers (23 women and 6 men), the median age was 58.5 [53; 62] years. In all participants flow cytofluorometry according to the standard technique with immunophenotyping of T- and B-lymphocytes was performed.Results and discussion. Compared to controls, patients in group 1 who had not previously received sDMARDs showed a transient increase in "switched" memory B-cells, transient B-cells, and plasmablasts, which was not observed in patients of group 2 (on sDMARDs therapy). Patients with advanced RA showed a statistically significant decrease in the absolute and relative number of memory B-cells, the absolute and relative number of "switched" B-lymphocytes, as well as the number of plasmablasts and transient cells. In RA patients, a statistically significant rela tionship was established between the number of swollen joints and the level of plasmablasts (r=0.51), memory cells (r=0.54), and "switched" B-cells (r=0.41), p< 0,05 in all cases. There were no statistically significant changes in other subpopulations of B-lymphocytes and the profile of T-lymphocytes.Conclusion. Changes in the B-lymphocyte profile are characteristic of different stages of RA. At an early stage, there is an increase in the number of transient B-lymphocytes, plasmablasts and plasmocytes, and in the advanced stage, a decrease in the level of certain populations of B-lymphocytes, such as memory B-cells and "switched" B-lymphocytes. It can be assumed that the ineffectiveness of sDMARDs is associated with a change in the population composition of B-lymphocytes, which requires further study.